Cavity ring-down spectroscopy with a laser frequency stabilized and locked to a reference target gas absorption for drift-free accurate gas sensing measurements - Liu, Ying; He, Yabai; Hu, Mai; Chen, Bing; Xu, Zhenyu; Yao, Lu; Wang, Xingping; Kan, Ruifeng (Frontiers in Physics, 2023)
A new gas sensor system with fast response and ultra-high sensitivity has been developed based on a combination of frequency modulation spectroscopy (FMS) and cavity ring-down spectroscopy (CRDS). The system consisted of two distributed feedback laser diodes (DFB-LDs) emitting at frequencies 6251.761 cm -1 (Laser-1) and 6257.762 cm -1 (Laser-2), respectively. A portion of Laser-1's output was used by a frequency modulation spectroscopy technique to lock its frequency precisely at a CO2 absorption peak, while the rest of its output was coupled to an optical ring-down cavity, together with the Laser-2 output. The Laser-2 operated at a non-absorbing frequency for realtime correction of any baseline ring-down time drift caused by environmental changes (e.g. temperature, pressure). Laser frequency stabilization achieved a 5-fold improvement in CRDS detection sensitivity. This new system was able to make measurements at a data rate of 9 Hz. Based on Allan deviation analysis, the absorbance detection limit of the system was 4.4 ×10 -11 cm -1 at an optimum averaging time of ~5 s, whereas the time-normalized sensitivity at 1 s was 7.3×10 -11 cm - 1 /Hz 1/2 . Measurements of atmospheric CO2 mole fraction were conducted and demonstrated its good performance and reliability. This sensor will be particularly suitable for making drift-free measurements over long periods, in the fields of environmental and industrial gas sensing.